2006
DOI: 10.1111/j.1524-4725.2006.32142.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery for Lentigo Maligna and Lentigo Maligna Melanoma using Mel-5 Immunostaining: University of Minnesota Experience

Abstract: MMS with Mel-5 immunostaining yielded excellent results in the treatment of LM and LMM, with only one recurrence noted in 200 patients. When an automated immunostainer was used, minimal time was added to each Mohs stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…This is comparable to the number of stages reported in other studies (range: 14-2.7) using various techniques. 10,11,13,14,19,24 The initial lesion sizes and postoperative defect sizes were similar in our retrospective analysis comparing the two techniques, with the final defect sizes similar to another study using a staged technique 14 and smaller than another study using MMS. 13 Thus, our staged technique may offer smaller surgical defects with similar margin control and stage number, likely leading to optimal tissue conservation associated with a high cure rate.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is comparable to the number of stages reported in other studies (range: 14-2.7) using various techniques. 10,11,13,14,19,24 The initial lesion sizes and postoperative defect sizes were similar in our retrospective analysis comparing the two techniques, with the final defect sizes similar to another study using a staged technique 14 and smaller than another study using MMS. 13 Thus, our staged technique may offer smaller surgical defects with similar margin control and stage number, likely leading to optimal tissue conservation associated with a high cure rate.…”
Section: Discussionsupporting
confidence: 67%
“…The use of melanocyte-specific immunostains may be associated with decreased recurrence rates with MMS. A recent study of 200 cases of LM/LMM treated by MMS with Mel-5 immunostaining showed a recurrence rate of 0.5% after a follow-up period of 38 months 10. However, few Mohs laboratories (\15% in a recent survey) currently utilize immunostains 6.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…24 The reliability of frozen sections for interpreting melanoma in situ compared with paraffin-embedded sections has been questioned with Zitelli et al 22 reporting 100% sensitivity and 90% specificity whereas others report lower sensitivity and specificity rates of 73% and 68%, respectively. 12 Immunostains with HMB-45, S-100, MART-1, and Mel-5 have been advocated 11,[25][26][27][28] to overcome frozen section difficulties of freeze artifact and distinguishing actinically damaged keratinocytes from melanocytes, but require additional processing time. An alternative approach is to use frozen sections until a negative margin is achieved and then confirm final margins with permanent sections.…”
Section: Discussionmentioning
confidence: 99%
“…While MEL-5 has been used for MS for melanoma [58,59], it is not considered the preferred immunostain owing to nonspecific immunostaining of melanosomecontaining cells, such as basal keratinocytes [8]; as a result, it may falsely stain pigmented actinic keratoses, pigmented Bowen's disease and lichen planus-like keratoses. MEL-5 also does not reliably stain amelanotic or desmoplastic melanoma and the dermal component of melanoma [60].…”
Section: Immunostainingmentioning
confidence: 99%